(untitled) (Fiep Bulletin - online, 2016)
The objective of the study was to relate the level of superior, lower strength, and abdominal handball athletes of both sexes in the sub 15 and U17, which were present in Paraná Cup Handball categories, sample of 291 individuals, which were classified by sex and sports category. Four groups were formed from the combination of two classes related to gender (female and male) and two classes of sports category (sub 15 and sub 17). The evaluated variables were: time in the sport (TE) in years, body mass (BM) in kg, height (H), trunk-cephalic height (ATC), body mass index (BMI), lower limb strength (IMF) abdominal strength and endurance (FRA), strength and trunk flexibility (FFT), upper limb strength (FS). The analysis was performed based on descriptive statistics. At higher values of strength of the upper limbs correspond to the highest values of the abdominal force, by the way, the increase in strength of the upper members provides a positive correlated response (increase) in the abdominal and back strength.